STATCOM – A Preface to Power Quality in Power Systems Performance - Jadeja, R.; Patel, S.; Chauhan, S. (Engineering, Technology & Applied Science Research, 2016)
This paper investigates different types of Flexible AC transmission System (FACTS) controllers with focus on various operational and control aspects of static synchronous compensators (STATCOM) to different performance characteristics like power transfer capability, voltage regulation, reactive power management, stability limits, power factor improvement etc. In addition, various features related to STATCOM like converter topologies, reference compensating signal generation schemes, controllers, and generation of switching signals are reviewed.